Influence of the energy and protein levels in ration on the onset of puberty and semen quality in male Holstein - Alvarez, J.L.=700 1 Zaldivar, V.; Boado, A.; Lannes, M.; Tamayo Aviles, A.; Faure, R.
(En, Es)
Ilus., 33 ref.
Keywords: GANADO BOVINO; MACHO; ENERGIA; PROTEINAS; MADURZ SEXUAL; LIBIDO; TESTOSTERONA; PESO CORPORAL; CALIDAD; SEMEN; CUBA; DEGENERACION TESTICULAR; MACHO HOLSTEIN; REVISTA DE SALUD ANIMAL